Ex vivo comparison of intradermal closures with conventional monofilament suture vs unidirectional barbed suture in dogs. Issue 8 (4th July 2019) - Regier, Penny J.; Smeak, Daniel D.; McGilvray, Kirk C.
Abstract: Objective: To evaluate the mechanical properties, strength, and quality of seal provided by continuous intradermal suture lines closed with barbed suture vs monofilament suture. Study design: Experimental study. Sample population: Forty‐eight full‐thickness wounds in canine cadavers. Methods: Four‐centimeter‐long parasagittal cutaneous wounds were created in canine cadavers. Each intradermal closure was closed with smooth monofilament suture and terminated with a 2 + 1 Aberdeen knot (n = 24) or a unidirectional barbed suture terminated with a single end pass (n = 24). Wounds (n = 12/group) were harvested, and a servohydraulic machine applied tensile load perpendicular to the long axis of the suture line. A load–displacement curve was generated; maximum load, displacement, stiffness, and mode of construct failure were recorded. Harvested wounds were placed in a watertight construct to measure the volume of fluid leaking over 3 minutes at 1.0 ± 0.1 psi. Results: Stiffness did not differ between constructs ( P  > .05). Incisions closed with monofilament sutures sustained higher maximum load (311.21 N ± 87.40) and displacement at failure (21.19 mm ± 4.51) compared with those with barbed sutures (116.38 N ± 42.82 and 15.03 mm ± 2.32, respectively, P  < .05). Closures with monofilament sutures leaked more (4.38 mL ± 7.90) compared with those with barbed sutures (0.15 mL ± 0.43, P  < .05). Conclusion: Monofilament sutures resulted in stronger constructs, whereas barbed suture constructs provided a better watertight seal. Clinical significance: While unidirectional barbed sutures may improve watertight skin closure, surgeons should consider using conventional monofilament sutures when mechanical strength of the closure is of primary concern.